Unilateral renal agenesis and proximal blind-ending ureter with ureteric atresia - Maity, Krishnendu; Satardey, Ritesh; Pal, Dilip Kumar (Indian Journal of Case Reports, 2020)
Renal agenesis associated with proximal blind-ending ureter, ureteric atresia, and fusiform dilatation of distal ureter which is an extremely rare occurrence and has not been described in the literature. We report a case of unilateral renal agenesis and ipsilateral proximal blind-ending ureter with ureteric atresia in an 11-year-old boy which was dealt surgically with good outcomes.